Impact of activity types and speaking hours on spoken English fluency: a comparative study in Bangladeshi tertiary classes - Haque, Md. Nurul; Dahal, Niroj; Hasan, Md. Kamrul; Manandhar, Netra Kumar; Sharmin, Sumona (Frontiers in Education, 2025)
The correlation between classroom activity kinds and the duration of student speaking time is essential for enhancing fluency in spoken English. This study investigates the effect of activity types and talk time on developing fluency in spoken English among Bangladeshi tertiary-level students. It used a comparative methodology, looking at two classes: a class that was taught using interactive activities (e.g., role-plays, group discussions) with 30 h of spoken practice and a class that focused on monologic activities (e.g., presentations, storytelling) with 20 h of spoken practice. Fluency improvements were evaluated via pre-tests and post-tests, while classroom observations, surveys, and interviews provided a deeper look at the attitudes of students and teachers. The quantitative analysis revealed that Class A, with interactive tasks and more speaking hours, made significantly greater progress with fluency than Class B, and qualitative results also supported the value of interactive tasks in promoting engagement and confidence. It was also found that combining grouped activities and long speaking hours improved fluency. Practical matters include adding more interactive activities to new course offerings and giving them ample time to speak. Such a study will contribute to the current knowledge of English language teaching and learning in a bilingual context with clear pedagogical implications and practices for teachers in Bangladesh and similar contexts.